Five years follow-up of a keratocyst odontogenic tumor treated by marsupialization and enucleation: A case report and literature review - Rafael Scaf de Molon; Mario H Verzola; Luana C Pires; Vinicius I Mascarenhas; Rodrigo B da Silva; Joni A Cirelli; Roberto H Barbeiro (Wolters Kluwer Medknow Publications, 2015)
Odontogenic cysts are considered as nonneoplasic benign lesions. Among the cysts, keratocyst odontogenic tumor (KCOT) is an intra-osseous tumor characterized by parakeratinized stratified squamous epithelium and a potential for aggressive, infiltrative behavior, and for the possibility to develop carcinomas in the lesion wall. Thus, the aim of this study was to describe a clinical case of KCOT in a young patient and discuss the treatment alternatives to solve this case. A 15-year-old male was referred for treatment of a giant lesion in his left side of the mandible. After the biopsy, a diagnostic of KCOT was made, and the following procedures were planned for KCOT treatment. Marsupialization was performed for lesion decompression and consequent lesion size reduction. Afterward, enucleation for complete KCOT removal was performed followed by third mandibular molar extraction. After 5 years, no signs of recurrence were observed. The treatment proposed was efficient in removing the KCOT with minimal surgical morbidity and optimal healing process, and the first and second mandibular molars were preserved with pulp vitality. In conclusion, this treatment protocol was an effective and conservative approach for the management of the KCOT, enabling the reduction of the initial lesion, the preservation of anatomical structures and teeth, allowing quicker return to function. No signs of recurrence after 5 years were observed.